Recurrent issues in the narrative proposal by José Jiménez Lozano (XXI Century. Spanish Literature and Culture, 2020)
This article discusses the concept of José Jiménez Lozano´s narrative as a meeting place of his ethic and aesthetic interests, analysing the importance of the ideals of tolerance and truth, inherent to his work, and summarising the notions on which the concept of the writer´s narrative lies. Coming from the difference among three different fields in this narrative proposal, based on the thematic coincidences, the intertextual relationships and the aesthetic attitude are summarised and analyse the themes that are repeated in different works.
Keywords: Aesthetics; narrative; Ethics; Intertextuality; José Jiménez Lozano